решите уравнение (3X+1) ^ (2) = 40+9 (x-1) (x+2)

+1
Ответы (1)
  1. 18 февраля, 01:23
    0
    Решим уравнение.

    (3 * X + 1) ^2 = 40 + 9 * (x - 1) * (x + 2);

    Раскроем скобки.

    (3 * x) ^2 + 2 * 3 * x * 1 + 1^2 = 40 + 9 * (x * x + 2 * x - 1 * x - 2 * 1);

    3^2 * x^2 + 6 * x + 1 = 40 + 9 * (x^2 + 2 * x - x - 2);

    9 * x^2 + 6 * x + 1 = 40 + 9 * (x^2 + x - 2);

    9 * x^2 + 6 * x + 1 = 40 + 9 * x^2 + 9 * x - 9 * 2;

    9 * x^2 + 6 * x + 1 = 40 + 9 * x^2 + 9 * x - 18;

    9 * x^2 + 6 * x + 1 - 9 * x^2 = 40 + 9 * x - 18;

    Приведем подобные слагаемые.

    6 * x + 1 = 40 + 9 * x - 18;

    6 * x + 1 = 9 * x + 22;

    6 * x - 9 * x = 22 - 1;

    -3 * x = 21;

    x = - 21/3;

    x = - 7.
Знаешь ответ на этот вопрос?